PERSEPSI MASYARAKAT TENTANG PENYEBAB TERJADINYA BANJIR DI BATANG TAMING NAGARI BATAHAN KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Andrajani, Nova; Dasrizal, Dasrizal; Farida, Farida (STKIP PGRI Sumbar, 2013)
This aims of this study is to describe and analyze public perception the parameters to be analyze on The Causes Flooding in Nagari Taming Batahan West Pasaman, views of: 1) Deforestation. 2) Amount of garbage pile .3) Limitations of flood control infrastructure. This study used qualitative methods. Research informants are people who live in Nagari Taming Batahan Sub Domains Batahan West Pasaman. Sampling was done by using key informants, data were collected by interview and documentation as well as active participation of investigators.The data collected were analyzed using the techniques of Reducation. Presentation of data, verification and conclusion. The results showed that, first in terms of the logging that they are clearing forests to clear land for plantations, and there are also people who take the timber to be processed and made into boards. Secondly, based on the public perception in terms of the many piles of garbage they claim that many trash piles will cause flooding, because the garbage will clog drains and ucan- varions diseases. Third, based on the perception of society in terms of facilities and infrastructure limitations that in the flood area.Based on the above explanation, the researchers described the cause of flooding in the trunk Taming Nagari Batahan sub district of Batahan West Pasaman cause by. Deforestation, many piles of garbage, and limitation of flood facilities and infrastructure.